Problems of Determining Suspect Against a Deceased Person In The Investigation Process - Jamaludin, Ahmad (Dinasti Research, 2024)
Bringing judicial proceedings against the body or memory of a deceased defendant was once possible, but this is no longer possible in today’s world, as criminal actions must be stopped even before a deceased complainant is named as a suspect. This research aims to examine the criminal justice system in Indonesia regulating the status of cases against the determination of a suspect in a person as a witness/reported person who has first died. The research method used in this study is normative juridical. According to the findings of the study, the current Criminal Procedure Code cannot provide an adequate answer regarding the validity of the determination of a suspect against a deceased person, because it only states that the investigation must be stopped if the suspect dies, which implies that the suspect should have been determined during the investigation process. Therefore, lawmakers should make rules regarding the mechanism for investigations when the reported or suspected guilty person dies. Because in fact, the death of a person as a reported person suspected of committing a criminal offense requires the termination of the criminal case because the legal subject who should be held accountable for the criminal offense has died.